ANALISIS KESULITAN SISWA DALAM MEMAHAMI KONSEP DAN MENYELESAIKAN SOAL ALJABAR - Agisna Maulana; Nasywaa Nuur; Edelweis Yuniar; Indah Retnowati; Ahmad Fuadin (Universitas Palangka Raya, 2023)
This research is aim to describe the difficulties in learning and solving Algebra problems experienced by class VII Students of SMP Negeri 7 Cimahi. This research method uses a descriptive method with a qualitative approach. The subjects used in this research were five Students of class VII H who were randomly selected, and the teacher concerned. The instrument used in this study were written tests, questionnaires and interview guides. The results of this research indicate the various difficulties experienced by Students and the factors that cause them. These difficulties include difficulties in identifying coefficients, determining like terms, and performing various arithmetic operations in Algebraic forms. The factors that cause Student difficulties are divided into two, namely internal and external factors. The internal factor is that Students don't understand the concept and don't master arithmetic operations on integers, while the external factor is the lack of Interest, talent and motivation of Students in learning Algebra.